Reimagining Fugitive Democracy and Transformative Sanctuary with Black Frontline Communities in the Underground Railroad. (October 2019) - Haro, Lia; Coles, Romand
This article engages new histories of the black frontline communities of the Underground Railroad to rethink both fugitive democracy and the transformative possibilities of sanctuary as its constitutive twin. We analyze the ways that communities of free blacks and fugitives in the border zones between the Antebellum US North and South crafted themselves as magnetic spaces of creative refuge that suggest we reconceive sanctuary as the generative twin of fugitivity. This insight enables us to theorize new ethical and political dimensions of Sheldon Wolin's concept fugitive democracy by illuminating how fugitivity as flight away from danger can be interwoven with sanctuary as flight into and toward alternatives. Specifically, we theorize three dimensions of fugitive democracy/transformative sanctuary—sanctuary tending, dramatic sanctuary, and disruptive hospitality. While some theorists have considered key motifs in Wolin's fugitive democracy to be opposed to vital themes disclosed in contemporary theories of black fugitivity, we argue that the power of black frontline communities stemmed precisely from their capacities to dynamically entangle political approaches (mis)taken to be at odds. For example, we suggest a theory and practice of tending involving both nurturing care and militantly defensive action, dramatic sanctuary performances that amplify public power by oscillating between tricky concealment and flagrant publicity, and disruptive hospitality that interweaves law-breaking harbor with strategies for juridical and institutional change. These insights open onto an alternative imaginary that can also provide a toolbox for building grassroots democratic power today, particularly in the face of emergent neofascism and escalating displacement worldwide.